A Cell Culture Platform for the Cultivation of Cryptosporidium parvum. Issue 1 (8th February 2019) - Jossé, Lyne; Bones, Alexander J.; Purton, Tracey; Michaelis, Martin; Tsaousis, Anastasios D.
Abstract: Cryptosporidium is a genus of ubiquitous unicellular parasites belonging to the phylum Apicomplexa. Cryptosporidium species are the second largest cause of childhood diarrhea and are associated with increased morbidity. Accompanying this is the low availability of treatment and lack of vaccines. The major barrier to developing effective treatment is the lack of reliable in vitro culture methods. Recently, our lab has successfully cultivated C. parvum in the esophageal cancer–derived cell line COLO‐680N, and has been able to maintain infection for several weeks. The success of this cell line was assessed with a combination of various techniques including fluorescent microscopy and qPCR. In addition, to tackle the issue of long‐term oocyst production in vitro, a simple, low‐cost bioreactor system using the COLO‐680N cell line was established, which produced infectious oocysts for 4 months. This chapter provides details on the methodologies used to culture, maintain, and assess Cryptosporidium infection and propagation in COLO‐680N. © 2019 by John Wiley & Sons, Inc.